Karakter dan Adab Pendidik Perspektif al-Qur’an dan Hadis - Muhammad Azka Maulana; Yoyo Rodiya (AL-MUFASSIR, 2022)
Educators are figures who are always imitated and spearhead the success of education. Therefore, he needs to have character and ethics that are appropriate to his position as a role model that can support the success of the education. The character and etiquette of educators in this study were discussed through the study of the interpretation of the Koran and Hadith related to educational verses. The purpose of this study is to describe the character and etiquette of educators in the perspective of the Koran and Hadith. The results show that there are concepts of character values ??and etiquette sourced from the Koran and Hadith, including religious characters, responsibility, sincerity, patience, learning, and so on. heart, ease, fun and so on.